Prediction of Significant Prostate Cancer in Equivocal Magnetic Resonance Imaging Lesions: A High-volume International Multicenter Study - Sigle, August; Borkowetz, Angelika; Hardenberg, Jost von; Drerup, Martin; Kornienko, Kira; Kwe, Jeremy; Wenzel, Mike; Mandel, Philipp; Westhoff, Niklas Christian; Rieger, Constantin; Hoffmann, Manuela A.; Ortner, Gernot; et al. (European urology focus, 2023)
Background - Decision of performing prostate biopsy in men with Prostate Imaging Reporting and Data System (PI-RADS) 3 findings in prostate magnetic resonance imaging (MRI) is challenging as they have a low but still relevant risk of harboring significant prostate cancer (sPC). - Objective - To identify clinical predictors of sPC in men with PI-RADS 3 lesions in prostate MRI and to analyze the hypothetical effect of incorporating prostate-specific antigen density (PSAD) into biopsy decision. - Design, setting, and participants - We analyzed a retrospective multinational cohort from ten academic centers comprising 1476 men who underwent a combined prostate biopsy (MRI targeted plus systematic biopsy) between February 2012 and April 2021 due to a PI-RADS 3 lesion in prostate MRI. - Outcome measurements and statistical analysis - The primary outcome was the detection of sPC (ISUP ≥2) in a combined biopsy. Predictors were identified by a regression analysis. Descriptive statistics were applied to evaluate the hypothetical effect of involving PSAD into biopsy decision. - Results and limitations - Of all patients, 273/1476 (18.5%) were diagnosed with sPC. MRI-targeted biopsy diagnosed fewer sPC cases than combined strategy: 183/1476 (12.4%) versus 273/1476 (18.5%), p < 0.01. Age (odds ratio [OR] 1.10 [95% confidence interval CI: 1.05-1.15], p < 0.001), prior negative biopsy (OR 0.46 [0.24-0.89], p = 0.022), and PSAD (p < 0.001) were found to be independent predictors of sPC. Applying a PSAD cutoff of 0.15, 817/1398 (58.4%) biopsies would have been avoided at the cost of missing sPC in 91 (6.5%) men. Limitations were the retrospective design, heterogeneity of the study cohort due to the long inclusion period, and no central revision of MRI. - Conclusions - Age, previous biopsy status, and PSAD were found to be independent predictors of sPC in men with equivocal prostate MRI. Implementation of PSAD into biopsy decision can avoid unnecessary biopsies. Clinical parameters such as PSAD need validation in a prospective setting. - Patient summary - In this study, we looked for clinical predictors of significant prostate cancer in men with Prostate Imaging Reporting and Data System 3 lesions in prostate magnetic resonance imaging. We identified age, previous biopsy status, and especially prostate-specific antigen density as independent predictors.